Correlation of ten non-metric dental traits between deciduous and permanent molars of three ethnic colombian groups. - Ocampo, Ángela; Sánchez, Juan David; Martínez Cajas, Carlos Humberto; Moreno, Freddy (Revista Estomatología, 2009)
Summary Objective: To determine correlations of ten non-metric dental crown traits NMDCT (Carabelli, hipocon2, enamel bridge, metaconule, protostylid, deflecting wrinkle, pattern cusp, cusp number and 6 and 7 cusp) between deciduous second upper (um2) and low (lm2) molars, permanent first upper (UM1) and lower (LM1) molars and permanent second upper (UM2) and lower (LM2) molars were studied. Materials and Methods: This descriptive study determines the correlation of ten NMDCT through of the frequency and variability, observed on 201 dental casts of Cali racially mixed population, 84 dental casts of Puerto Tejada African-Colombian population and 60 dental casts of Colombian Amazons natives. Results: The Colombian Amazon natives showed high correlation in Carabelli and cusp number between um2/UM1; and very high in metaconule and pattern cusp. Cali racially mixed population showed moderated correlation in Carabelli, deflecting wrinkle and pattern cusp between um2/UM1; and high in 6 cusp. And between UM1/UM2/LM1/LM2 moderate in deflecting wrinkle; and high in protostylid, pattern cusp and 6 cusp. Puerto Tejada African-Colombian population showed moderated correlation between UM1/UM2/LM1/LM2 in deflecting wrinkle; and high in protostylid, pattern cusp and 6 cusp. Conclusions: Findings support the proposal of morphogenetic field theory, which exposes that the key tooth in deciduous and permanent molars is um2/lm2 because it retains the basic configuration of contact and number of cusps pattern, so UM1/UM2/LM1/LM2 will vary according to ethnic origin and to the environmental influence of each ofn three studied ethnic groups. Key words: Dental anthropology. Dental morphology. Non-metric dental traits. Deciduous dentition. Permanent dentition. Correlations.